Amygdala network dysfunction in late-life depression phenotypes: Relationships with symptom dimensions. (November 2015) - Li, Wenjun; Ward, B. Douglas; Xie, Chunming; Jones, Jennifer L.; Antuono, Piero G.; Li, Shi-Jiang; Goveas, Joseph S.
Abstract: The amygdala, a crucial hub of the emotional processing neural system, has been implicated in late-life depression (LLD) pathophysiology. However, the overlapping and diverging amygdala network function abnormalities underlying two clinical LLD phenotypes (i.e., LLD alone and LLD with mild cognitive impairment [LLD-MCI]) are unknown. The aim of this study is to investigate the amygdala functional connectivity (FC) differences between LLD alone, LLD-MCI and healthy controls, and to examine the relationships between amygdala network dysfunction and symptom dimensions. A resting-state functional connectivity magnetic resonance imaging study was conducted to probe amygdala FC in a total of 63 elderly participants (LLD [n = 22], LLD-MCI [n = 15], and age- and gender-equated healthy older adults [n = 26]) using a seed-based voxelwise R-fcMRI approach. LLD-only adults showed increased FC in the posterior default mode and vermis, and diminished connections in the fronto-parietal, salience and temporal areas, relative to controls. The LLD-MCI participants showed diminished FC in the default mode, cognitive control, salience and visual regions, whereas increased FC was limited to lateral parietal cortex compared with healthy controls. The LLD-MCI group also showed diminished FC in the occipital and posterior default mode areas, relative to the LLD-only group. Distinct amygdala FC abnormalities that explain depressive and anxiety symptom severity, and executive functioning were identified. The amygdala FC impairments may distinguish LLD phenotypes. These functional network abnormalities may also explain the heterogeneity seen in the LLD clinical presentations. Highlights: Diminished amygdala FC with executive control and increased FC in posterior default mode (pDMN) regions is seen in LLD. Dampening in the enhanced amygdala-pDMN FC is seen in LLD with MCI (LLD-MCI) patients. Globally decreased amygdala FC with emotional processing regions is seen in LLD-MCI. Amygdala FC alterations that explain symptom variations were found in LLD groups. Distinct amygdala FC may distinguish different LLD phenotypes and symptom dimensions.